Vaccine Development Against SARS-CoV-2: From Virology to Vaccine Clinical Trials - Kardani, Kimia; Bolhassani, Azam (Coronaviruses, 2021)
An urgent vaccine development is required against the recent pandemic of a novel coronavirus. Currently, there is no approved vaccine against COVID-19. Vaccination is proved to be the most beneficial way to protect humans from infections. Several vaccine candidates have been conducted to different phases of clinical trials, and more vaccine candidates are on the way to enter the trials. Different vaccine types have developed, including inactivated virus vaccines, subunit-based vaccines, adenovirus- vector vaccines, DNA-based vaccines, DC-based vaccines, and mRNA-based vaccines. The mRNA- 1273 was the first vaccine candidate that started evaluating in the clinical trial. Also, AZD1222 is the first vaccine candidate that started phase II/III of clinical trials. Both of these vaccine candidates were considered as promising vaccine candidates against SARS-CoV-2. This review aims to overview and share various strategies to develop efficient therapeutic and preventive vaccines based on the origin, biology, structure, and immune-evasion of SARS-CoV-2.
Keywords: life cycle